2006
DOI: 10.1002/polb.20948
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of the reaction‐induced phase separation of solutions of random copolymers of methyl methacrylate and N,N‐dimethylacrylamide in the precursors of a polythiourethane network

Abstract: Poly(methyl methacrylate) and random copolymers of methyl methacrylate (MMA) and N,N-dimethylacrylamide (DMA) containing 7.5, 15, or 20 wt % DMA were dissolved in a stoichiometric mixture of m-xylylene diisocyanate and 4-mercaptomethyl-3,6-dithia-1,8-octanedithiol, precursors of a polythiourethane network. Phase separation, which took place during polymerizations at 60, 90, and 120 8C, exhibited a lower critical solution temperature behavior. The cloud-point conversions, which were determined by the iodometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…An implicit assumption of eq 7 is that the quality of the solvent (E) is the same in the conversion range of the experimental cloud-point conversions. One of the required values of interaction energies was previously reported: B MMA - DMA = +11.6 J/cm 3 . The two remaining values were taken as fitting parameters using the procedure described below.…”
Section: Resultsmentioning
confidence: 98%
“…An implicit assumption of eq 7 is that the quality of the solvent (E) is the same in the conversion range of the experimental cloud-point conversions. One of the required values of interaction energies was previously reported: B MMA - DMA = +11.6 J/cm 3 . The two remaining values were taken as fitting parameters using the procedure described below.…”
Section: Resultsmentioning
confidence: 98%
“…The highly elastomeric and tough mechanical properties of polyurethanes result from a segmented molecular structure consisting of at least two dissimilar phases along the backbone. Polythiourethanes, as a member of the polyurethane family, are characterized by high refractive index values and biocompatibility as well as strong hydrogen bonding with accompanying outstanding mechanical properties. However, polythiourethanes as elastomers have not been reported because of the absence in availability of flexible long-chain polythiols. In this study, thiol−acrylate and thiol−isocyanate reactions which have many of the attributes of click chemistry including high efficiency, little side products, benign catalysts, and high reaction rates were used to synthesize segmented polythiourethanes; we note that in this work we used an organic solvent in which the oligomers and polymers were soluble.…”
Section: Resultsmentioning
confidence: 99%
“…This, combined with the well-known optical and mechanical (flexibility) advantages of thiourethane and sulfide groups in polymer chains, would result in significant potential for the synthesis of useful linear segmented polythiourethane elastomers. It has already been reported that the addition of difunctional thiols to difunctional isocyanates leads to the formation of simple nonsegmented polythiourethanes, , which are classified as members of the polyurethane family with the hydrogen-bonding features that typically accompany polyurethanes. ,, In addition to synthesizing polythiourethanes by thiol−isocyanate step growth polymerization processes, polythiourethanes made from cyclic dithiocarbonates by living cationic polymerization have been reported by Endo et al The use of these linear, nonsegmented polythiourethanes, characterized by controllable molecular weights and narrow molecular weight distributions resulting from the living cationic polymerization process, is limited to applications requiring glassy materials and/or highly dense cross-linked structures. , Since sulfide linkages incorporated into aliphatic polyesters have been reported to lead to the unique combination of flexible films with low glass transitions and high degrees of crystallization, it is expected that the synthesis of segmented polythiourethanes with sulfide linkages in the soft segment would open up a new potential for elastomers with a unique combination of properties. While it is possible to use a combination of short chain dithiols and oligomeric polyols to make segmented elastomeric poly(thiourethane−urethane)s, incorporation of sulfide linkages in the soft segment oligomer would certainly lead to a set of new polymers with high flexibility and enhanced crystallinity.…”
Section: Introductionmentioning
confidence: 99%